FACTORS AFFECTING PURCHASING DECISION OF ON LITERATURE E-BOOKS OF THAI READERS (Journal of Namibian Studies : History Politics Culture, 2023)
Purpose: The purpose of this research is to study the factors that influence purchasing decision on literature e-books of Thai readers.Theoretical framework: The theory was intended to explain Thai readers’ purchasing decision on literature e-books, which is determined by three factors: motivation, technology acceptance, and performance expectations. Purchase decision is the thought process that leads a consumer from identifying a need, generating options, and choosing a specific product and brand.Design/methodology/approach: The study constructs a model to explain the causal factors in relation to motivation, technology acceptance, performance expectation, and purchasing decision. Data was collected from a sample group of 352 purchased on literature e-books in Rayong, Bangkok and Chonburi Province using online questionnaires.Findings: It was found that technological acceptance has the greatest influence on the purchasing decision of e-books. Furthermore, technological acceptance is still full mediator between motivation and purchasing decision of e-book.Research, Practical & Social implications: We recommend that the future research should have widen areas for results calibration.Originality/value: The results indicate that these findings can guide the government supports and encourages entrepreneurs to produce electronic books (e-book) in the genres of novels and literature to have a variety. Including extending the results to entrepreneurs producing other types of e-books such as sports, tourism, etc. It will help reduce the use of paper and is a sustainable environmental conservation.